Cause of death during upper tract urothelial carcinoma survivorship: A contemporary, population-based analysis - Peng, Fu-Sheng; Wu, Wan-Ting; Zhang, Lu; Shen, Jia-Hua; Yu, Dong-Dong; Mao, Li-Qi (Frontiers in Oncology, 2022)
ABSTRACT BACKGROUND: Very few studies have been published on the causes in death of upper tract urothelial carcinoma (UTUC). We sought to explore the mortality patterns of contemporary UTUC survivors. METHODS: We performed a retrospective cohort study involving patients with upper urinary tract carcinoma from the National Cancer Institute’s Surveillance, Epidemiology, and End Results (SEER) database (2000 and 2015). We used standardized mortality ratios (SMRs) to compare death rates among patients with UTUC in the general population, excess absolute risks (EARs) to quantify the disease-specific death burden. RESULTS: A total of 10179 patients with UTUC, including 7133 who died, were included in our study. 302(17.17%) patients with localized disease died of UTUC, however, patients who died from other causes were 4.8 times more likely to die from UTUC (n = 1457 [82.83%]). Cardiovascular disease was the most common non-cancer cause of death (n = 393 [22.34% of all deaths]); SMR, 1.22; 95% confidence intervals [CI], 1.1–1.35; EAR, 35.96). 4046 (69.99%) patients with regional stage died within their followship, 1413 (34.92%) of whom died from UTUC, and 1082 (26.74%) of whom died from non-cancer causes. UTUC was the main cause of death (SMR, 242.48; 95% CI, 230-255.47; EAR, 542.47), followed by non-tumor causes (SMR, 1.18; 95% CI, 1.11-1.25; EAR, 63.74). Most patients (94.94%) with distant stage died within three years of initial diagnosis. Although UTUC was the leading cause of death (n = 721 [54.29%]), these patients also had a higher risk of death from non-cancer than the general population (SMR, 2.08; 95% CI, 1.67-2.56; EAR, 288.26). CONCLUSIONS: Non-UTUC deaths accounted for 82.48% of UTUC survivors among those with localized disease. Patients with regional / distant stages were most likely to die of UTUC, however, there is an increased risk of dying from non-cancer causes that can cannot be ignored. These data provide the latest and most comprehensive assessment of the causes of death in patients with UTUC.